2011
DOI: 10.1007/s00406-011-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

Parent of origin effect and allelic expression imbalance of the serotonin transporter in bipolar disorder and suicidal behaviour

Abstract: Suicide and suicidal behaviour are a major health concern worldwide particularly in patients with mood disorders. Family, adoption and twin studies show that genetics influences suicidal behaviour. The serotonin transporter (5HTT) plays an important role in the pathophysiology of mood disorders and may also be involved in suicidal behaviour since 5HTT binding is decreased in the brain of suicide completers. Because the effect of genomic imprinting in the 5HTT gene on suicidal behaviour has not been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Altamura et al (2010), Baumann et al (1999), Bellivier et al (2000), Benedetti et al (2011), Berrettini et al (1986), Campos et al (2010), D’Ambrosio et al (2012), De Luca et al (2005a, 2005b, 2006, 2009), Dowlatshahi et al (1999), Dracheva et al (2008), Evans et al (2012), Feldcamp et al (2008), Finseth et al (2014), Jimenez et al (2013), Kamali et al (2012), Kim et al (2002, 2007, 2008), Le-Niculescu et al (2013), Leszczynska-Rodziewicz et al (2014), Lopez et al (2007), Mahon et al (2012), Malloy-Diniz et al (2011), Matsuo et al (2010), Monfrim et al (2014), Nery et al (2014), Nery-Fernandes et al (2012), Neves et al (2008, 2010), Park et al (2013), Perlis et al (2012), Pinto et al (2011), Pompili et al (2008), Shabani et al (2013), Sher et al (2006, 2012), Singhal et al (2014), Souery et al (2001), Stange et al (2014), Suttajit et al (2013), Thibodeau et al (2013), Tidemalm et al (2014), Tochigi et al (2008), Tsai et al (1999a), Vuksan-Cusa et al (2009) and Willour et al (2012).…”
Section: Figurementioning
confidence: 99%
“…Altamura et al (2010), Baumann et al (1999), Bellivier et al (2000), Benedetti et al (2011), Berrettini et al (1986), Campos et al (2010), D’Ambrosio et al (2012), De Luca et al (2005a, 2005b, 2006, 2009), Dowlatshahi et al (1999), Dracheva et al (2008), Evans et al (2012), Feldcamp et al (2008), Finseth et al (2014), Jimenez et al (2013), Kamali et al (2012), Kim et al (2002, 2007, 2008), Le-Niculescu et al (2013), Leszczynska-Rodziewicz et al (2014), Lopez et al (2007), Mahon et al (2012), Malloy-Diniz et al (2011), Matsuo et al (2010), Monfrim et al (2014), Nery et al (2014), Nery-Fernandes et al (2012), Neves et al (2008, 2010), Park et al (2013), Perlis et al (2012), Pinto et al (2011), Pompili et al (2008), Shabani et al (2013), Sher et al (2006, 2012), Singhal et al (2014), Souery et al (2001), Stange et al (2014), Suttajit et al (2013), Thibodeau et al (2013), Tidemalm et al (2014), Tochigi et al (2008), Tsai et al (1999a), Vuksan-Cusa et al (2009) and Willour et al (2012).…”
Section: Figurementioning
confidence: 99%
“…Mendlewicz et al (2004) found no association for the 5-HTTLPR polymorphism with age-of-onset in BD or with BD in general ( N =572 BD cases). By contrast, Pinto et al (2011) did find a significant association between an earlier age of onset and the Short allele of the 5-HTTLPR polymorphism ( p =.02) in 350 BD patients and 693 unaffected relatives. Manchia et al (2010) and Mohammadi et al (2015) also found an association for earlier-onset and the Short allele of the 5-HTTLPR polymorphism in 230 and 150 BD patients, respectively.…”
Section: Candidate Gene-association Studiesmentioning
confidence: 66%
“…Neurotransmitter systems examined in BD cell models include adrenergic (Berrettini et al, 1987b;Kay et al, 1993;Kay et al, 1994;Wright et al, 1984), serotonergic (Pinto et al, 2011) and cholinergic (Lin and Richelson, 1986;Nadi et al, 1984); most studies have had negative results. The binding of 125 I-iodohydroxybenzylpindolol to β-adrenoceptors in BD LCLs has been examined (Berrettini et al, 1987b;Kay et al, 1993;Kay et al, 1994;Wright et al, 1984), but only one study found lower binding in BD.…”
Section: Neurotransmitter and Neuroendocrine Systemsmentioning
confidence: 96%